2012
DOI: 10.1001/jama.2012.91099
|View full text |Cite
|
Sign up to set email alerts
|

Facial and Upper Body Papules in a Patient With a Family History of Recurrent Pneumothorax

Abstract: 31-YEAR-OLD WOMAN PRESENTS WITH A 10-YEAR HISTORY OF PROGRESSIVE development of small, whitish/skin-colored papules across her forehead, neck, and upper back (FIGURE , A). She also has scattered skin tags in this distribution. The patient also reports that her brother and father have similar papular facial rashes, and her father has had recurrent pneumothoraces in the past, necessitating pleurectomy. A skin biopsy obtained from a representative lesion confirms the presence of fibrofolliculomas (Figure , B). Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 5 publications
1
5
0
6
Order By: Relevance
“…In agreement with other studies, (7)(8)(9) all patients of the present series presented with sudden onset of chest pain with shortness in breath. Noppen and de Keukeleire, (10) recorded that in the majority of cases pain usually resolves within one day even though pneumothorax still exists with signs indicating free air in the pleural space, a finding which was not recorded in our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with other studies, (7)(8)(9) all patients of the present series presented with sudden onset of chest pain with shortness in breath. Noppen and de Keukeleire, (10) recorded that in the majority of cases pain usually resolves within one day even though pneumothorax still exists with signs indicating free air in the pleural space, a finding which was not recorded in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Diagnosis of primary spontaneous pneumothorax is confirmed in most of the cases by chest x-rays, where the rim of air between the chest wall and the lung can be determined and used to assess accurately the pneumothorax size. (8)(9)(10) If the patient has a small pneumothorax chest CT can be used to confirm diagnosis along with detection of amount of air in pleural cavity, any blebs, or fluid collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The skins lesions can be removed surgically – or with laser therapy or curettage for cosmetic reasons, but they tend to recur [190-193]. A recent trial of topical sirolimus has shown no improvement with regard to the number and size of fibrofolliculomas in patients with BHD [194].…”
Section: Birt-hogg-dubé Syndromementioning
confidence: 99%
“…Dieses befindet sich auf Chromosom 17. Das Protein FLCN ist in unterschiedlichen Geweben lokalisiert, darunter auch in der Haut und im Lungen-und Nierenparenchym [8]. FLCN bildet einen Komplex mit den Proteinen FNIP1 und FNIP2, der wiederum mit Signalmolekülen wie AMPK und mTOR interagiert.…”
Section: Abstract !unclassified